OPTIMIZATION OF HUMAN RESOURCE MANAGEMENT: TECHNOLOGIES, STRATEGIES, AND LEADERSHIP - Gabit Dyussembayev; Nazym Zhunusbekova; Dinara Satybaldiyeva; Marat Kamysbayev (Theoretical Hypotheses and Empirical Results, 2025)
In today’s rapidly changing business environment, human resource (HR) management has become a critical factor in ensuring organizational sustainability. This article explores contemporary approaches to optimizing HR processes and the strategic development of personnel. The authors analyze the impact of digital technologies, such as artificial intelligence, cloud platforms, and big data analytics, on the transformation of HR functions. The study also examines motivation, corporate culture, and leadership as integral components of effective HR management. Based on the analysis of international and domestic experience, as well as recent research findings, the authors offer recommendations for enhancing the effectiveness of HR strategies. Particular attention is paid to the role of HR analytics in forecasting staffing needs and supporting decision-making. Leadership development and employee motivation tools are also discussed as elements of long-term HR strategy. The article presents a comprehensive overview of current trends and practices in HR management, emphasizing the integration of technological solutions with a human-centered approach to employee development. The findings may be useful for both researchers and practitioners interested in building an effective and adaptive HR system.